Culture-Based Indonesian Language Program for Foreign Speakers (BIPA) at BIPA Course Institutions in Yogyakarta - Haliq, Abdul; Akhiruddin, Akhiruddin; Ismail, Asri (Makassar State University, 2025)
Abstract. This study aims to analyze the Indonesian language teaching program for foreign speakers organized by the BIPA institution and how cultural integration in language learning enhances students' comprehension and language skills. This study seeks to answer two main questions: (1) What is the structure and implementation of the Indonesian language teaching program in BIPA institutions? (2) How does cultural integration in BIPA learning affect students' language acquisition? This study employed a qualitative approach, utilizing semi-structured interview and documentation as data collection methods. The collected data were analyzed through thematic analysis techniques involving coding, categorization, and interpretation of emerging patterns from interview responses and studied documents. The results show that BIPA programs can be categorized into two main types: (1) Indonesian for Academic Purposes (BIPATA) which focuses on linguistic aspects and their use in academic settings, and (2) Indonesian for Cultural Purposes, which emphasizes hands-on experience in a cultural context. Academic-based programs are conducted through classroom learning with a theoretical approach and language practice in a formal environment. Meanwhile, culture-based programs include activities outside the classroom, such as cultural camps, visits to historical sites and tourist attractions, jumparingan (traditional archery), and cultural workshops. Further analysis reveals that cultural integration in learning not only enriches participants learning experiences but also accelerates language acquisition through direct interaction with Indonesian society and cultural environment. Thus, this study highlights the significance of a culture-based approach in Indonesian language teaching for foreign speakers to enhance their communicative skills and contextual understanding of the language. Keywords: BIPA, culture, program, foreign learners